MODELLING THE EFFECTS OF HCV PLUS-STRAND RNA INFLUX INTO A CELL DURING HCV REPLICATION - Nafiu Hussaini (IndoMS, 2020)
This paper presents a sub-genomic Hepatitis C Virus (HCV) replication model which incorporates the rate of influx of HCV plus-strand RNA into Huh-7 cell and monitored its effects. The schematic diagram of HCV replication has been simplified. The model exhibits three equilibrium, namely: trivial equilibrium, healthy equilibrium and endemic equilibrium. Stability analysis of the model shows that the healthy equilibrium is globally asymptotically stable under certain condition. It is shown that increase in the rate of influx, increases the steady state level of total plus strand RNA, synthesized plus strand RNA, replicated plus strand RNA and NS5B in the system. Sensitivity and uncertainty analyses of the model (using the basic replication number (R_0) as the response function) show that the top three PRCC-ranked parameters are the rate of influx, k_0 of HCV plus-strand RNA, the rate of production of translation complex (T_c) and the rate of degradation, μ_p^cyt, of plus-strand RNA R_P^cyt. Furthermore, the distribution of R_0 is between [0.9999, 1.0008] with a mean of R_0=1.0003.